When is the fire spreading and when it travels? – Numerical simulations of compartments with wood crib fire loads. (December 2021) - Janardhan, Rahul Kallada; Hostikka, Simo
Abstract: The requirements for the occurrence of travelling fires and their distinction from previously recognized stages of fire development are not well understood. Here we present a CFD method that couples a fuel-area correction to a single-step wood pyrolysis model. The model was validated using SP medium-scale tunnel, demonstrating 19% under-prediction in peak HRR, and BST/FRS large-scale compartment where the predicted temperatures were within ±6% of the measurements. Detailed simulations of compartment geometries identified three modes of fire propagation: (1) With high ceiling heights, the ignition was followed by a fuel-controlled spread/travelling at speeds <1 cm/s (2) With lower ceiling heights, we observed a rapid (1–9 cm/s) spread towards the opening, driven by the smoke layer radiation and leading to a ventilation -controlled fire. (3) Finally, fire travelled back to the compartment interior at speed 0.1–0.9 cm/s, driven by large flames and controlled by the fuel-burnout. The analytical travelling fire model is designed to describe the first mode, but could also be used for modelling the back-travelling stage. Comparison between the CFD simulation and the analytical model indicates that further development of the analytical model is needed to account for the compartment's heating history and tunnel -like geometries.